2003
DOI: 10.1002/jbt.10062
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of cadmium‐induced oxidative damage and glucose‐6‐phosphate dehydrogenase expression through glutathione depletion

Abstract: The effect of cadmium (Cd), a significant environmental contaminant, on the expression of glucose-6-phosphate dehydrogenase (G6PDH), has been investigated. G6PDH is the key rate-limiting enzyme in the pentose pathway and the expression of its gene has been shown to be redox-sensitive. We show that incubation of primary rat hepatocytes with Cd induces oxidative stress in a time- and concentration-dependent manner as measured by increases in the cytotoxic parameters, lactate dehydrogenase (LDH) and lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…There is growing evidence that Cd up-regulates redox-sensitive signaling pathways such as MAPKs leading to increased expression of various genes (Xu et al, 2003;Rockwell et al, 2004). We also found that 2 M Cd increased phosphorylation of p38 MAPK, and a specific inhibitor of p38 MAPK, SB203580, blocked Cdinduced COX-2 expression and PGE 2 synthesis.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…There is growing evidence that Cd up-regulates redox-sensitive signaling pathways such as MAPKs leading to increased expression of various genes (Xu et al, 2003;Rockwell et al, 2004). We also found that 2 M Cd increased phosphorylation of p38 MAPK, and a specific inhibitor of p38 MAPK, SB203580, blocked Cdinduced COX-2 expression and PGE 2 synthesis.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, both p38 MAPK and JNK were activated but only p38 MAPK was responsible for COX-2 expression in mouse hippocampal cells exposed to Cd (Rockwell et al, 2004). In contrast, ERK pathway is known to be involved in Cd induction of G6PDH in rat hepatocytes (Xu et al, 2003). Thus, together with our finding, these results suggest that there are differences in cell type and species specificity in relation to activation of MAPKs and types of MAPKs involved in the induction of specific genes following Cd exposure.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that a lower concentration of Cd 2ϩ treatment increases the expression of G6PDH as measured by mRNA levels and enzyme activity in rat hepatocytes (Xu et al, 2003). Furthermore, it has been demonstrated that G6PDH activity in the ovary extract was not diminished with 1 mM Cd 2ϩ (Carattino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although these will not completely eliminate oxidation, peroxidation is not detectable using a thiobarbituric acid assay (6). More importantly, enhanced oxidation induces G6PD expression (39,40). Thus, if arachidonic acid was causing oxidative stress, an increase in G6PD expression would have been observed.…”
Section: Discussionmentioning
confidence: 99%